1995
DOI: 10.1123/ijsn.5.3.232
|View full text |Cite
|
Sign up to set email alerts
|

High School Athletes and Nutritional Supplements: A Study of Knowledge and Use

Abstract: Factors influencing nutritional supplement use by high school students were assessed. Comparisons were made between various groups of sports participants and non-sports participants. The Nutritional Supplement Use and Knowledge Scale was administered to 509 students. Mean supplement use score was 10.87 (SEM= 0.50, range 0-57). Mean knowledge score was 13.56 (SEM =0.16, range 1-21). Significant relationships (p< .01) were obtained for supplement knowledge with use, and supplement use with gender. ANOVA found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 11 publications
(15 reference statements)
1
37
0
2
Order By: Relevance
“…This may indicate the need for food-based nutritional interventions, as the relationship between dietary education and a positive effect on knowledge has been highlighted in other intervention studies. [1,13] Resorting to supplements as a means to build muscle mass rather than improving their diets is problematic. Although most players did not believe that supplements were required for peak performance, it is of concern that 68% believed that protein supplements were required for increasing muscle mass and almost half of the players believed that they could take creatine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may indicate the need for food-based nutritional interventions, as the relationship between dietary education and a positive effect on knowledge has been highlighted in other intervention studies. [1,13] Resorting to supplements as a means to build muscle mass rather than improving their diets is problematic. Although most players did not believe that supplements were required for peak performance, it is of concern that 68% believed that protein supplements were required for increasing muscle mass and almost half of the players believed that they could take creatine.…”
Section: Discussionmentioning
confidence: 99%
“…This despite the fact that the international consensus on creatine use suggests that it should be limited to experienced and well-matured athletes, because it may lead to increased injuries and have a gateway effect. [4,5] Several international studies [4][5][6][10][11][12][13] of both elite and school-level adolescents in Western countries have indicated that supplements are commonly used, particularly by athletes who do weight training. In international research the type of supplements most commonly used varied somewhat depending on the study, but included multivitamins and single-nutrient supplements, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Em geral, a suplementação da dieta parece ser motivada pela preocupação com a saúde, associada à avaliação negativa da própria dieta e realizada como uma prática preventiva por quem acredita em seus benefícios.…”
Section: Discussionunclassified